EFEKTIVITAS PENGGUNAAN MEDIA BOARD GAME TERHADAP PENINGKATAN HASIL BELAJAR SISWA - Hadi Gunawan Sakti; Baiq Sarlita Kartiani (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2023)
Abstract: Based on observations made at SMKN 1 Lingsar, it was found that the learning process still uses conventional methods and modules as learning media so that student interest and learning outcomes are low. To overcome this, interesting and fun learning is applied, one of which is by using the learning media